UNEMPLOYMENT AND ITS EFFECTS ON THE CRIME RATE OF BAYELSA STATE, NIGERIA - Otodo, Ifeanyichukwu; Amabienimigha, Felix (EBSU Journal of Social Sciences and Humanities, 2024)
The paper examines the effects of unemployment on the Crime rate of Bayelsa State, Nigeria. The major focus of the study is to examine the major causes of unemployment in Nigeria; identify the level of crime in Nigeria and to bring it down to its effects on Bayelsa State. A cross sectional survey design was adopted on the study. Data for the study depends on both primary and secondary sources. Primary data were collected with the aid of a self- design structured questionnaire while secondary sources of data depend on the reviews of empirical literature of scholars. The Durkhemain “Anomie Theory” was implored as a sketch for theoretical framework of the study. Furthermore, a sample of 200 respondents were drawn using both purposive and simple random techniques, Yenagoa metropolis were selected randomization method of balloting was employed to select the respondents. Data selected were analyzed with frequency distribution table and simple percentage. The findings of the paper revealed that the major causes of crime in Bayelsa Stat are unemployment, poverty, government neglect and rising population and corruption. The paper concluded that unemployment is the major cause of high crime rate in Nigeria. The paper recommends among other that, government should create an enabling environment for industry to serve, youth should be creative and learn different vocational skills. The war against corruption should be intensified to ensure the fair distribution of resources. Unemployment is the root cause of crime rate and if it is properly tackled the level of crime will reduce drastically.